Некомпенсированные вюрмские вымирания. Сообщение 4. Старый Свет: смягченный кризис - Пучков, П.В. (Вестник зоологии, 1993)
The early (from Eopleistocenic times) beginning of the uncompensated impoverishment of Quaternary megafauna of Africa and Eurasia is due to the early acquirement by hominids the skill for killing the largest herbivores, the edificators of ecosystems. But the coevolution of giants and other animals with hominids facilitated them the adaptation to direct and indirect anthropic influences. The development of the crisis was inhibited also by the largest carnivores, powerful foes and competitors of hominids. The improvement of weapons, perfection of social organisation, psychical and physical qualities, the mastering of fire and the symbiosis of man with «pre-dogs> (anthropophilic ecotypes of wolves and probably, to a lesser extent, these of jackals and extinct Eurasian coyotes) gradually emancipated mankind from the pression of large carnivores. The completion of this arduous and long-standing process together with other factors resulted in the increase of Late Paleolithic population in comparison to the Middle Paleolithic one and, consequently, led* to an acceleration of the process of man-induced extinctions. In the Palearctic the rivalry of man with the largest predators was more acute, than in Palaeotropis, because of the shortage of food sources alternative to the megafauna. For the same reason primitive hunters persued gigantic herbivores in northern regions more zealously than in southern ones. For this and some subsidiary reasons North Eurasia lost all its pachyderms, whereas in Paleotropis populations of the species more resistant to human predation ousted less resistant species. So extant species of elephants mastered all the variety of biotopes of their regions, previously divided between several species of proboscidians. Due to the survival of some gigantic herbivores conditions of existence for other Palaeotropical megafauna underwent only moderate changes. But for some species even these changes were baneful. Probable scenarios of their extinctions are discussed in this article.